The Relationship between Serum Iron and Thyroid Function in the Patients with Type 2 Diabetes - Wang, Congcong; Wen, Song; Yuan, Xinlu; Zhou, Mingyue; Li, Yanyan; Gong, Min; Jin, Jianlan; Zhou, Ligang (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2023)
Purpose: Our primary objective in this study is to determine the relationship between serum iron (Fe3+) and thyroid functions in type 2 diabetes mellitus (T2DM) patients. Materials and Methods: Glucose metabolic parameters, trace elements, such as Fe3+, and thyroid functions for 1657 type 2 diabetic patients treated at the Shanghai Pudong Hospital's Department of Endocrinology from 2018 to 2021 were assessed. Results: Variations in free thyroid hormones (FTH) and total thyroid hormones (TTH) were insignificant; however, thyroid-stimulating hormone (TSH) levels were markedly elevated in patients with positive thyroid peroxidase antibody (TPOAb) and/or positive antithyroglobulin antibody (TgAb) (p<0.05). Additionally, gender disparities affected FTH levels (p<0.05) but not TTH and TSH levels. The female gender was significantly negatively correlated with serum Fe levels (r=-0.381, p<0.05). Serum Fe3+ deficiency also had an effect on FT3 in both genders, FT4 and TT4 in males (p<0.05), but not TSH (p>0.05). The multilinear regression model showed that TT3 (β=0.702), eGFR (β=0.109), Fe3+ (β=0.003), female gender (β=-0.061), and age (β=-0.061) were the major determinants for FT3 change. Moreover, renal function, which was represented as the estimated glomerular filtration rate (eGFR), had no effects on Fe3+ and TSH levels but on the levels of FTH and TTH (p<0.05). FT3/FT4 exhibited correlations with Fe3+ (r=0.252) and eGFR (r=0.285). Finally, changes in Fe3+ levels had no significant impact on fasting plasma glucose (FPG), fasting C-peptide, HbA1c, and glycated albumin levels (p>0.05). Conclusion: In addition to age, gender, and renal functions, serum Fe3+ levels in T2DM patients have a significant relationship with thyroid functions.
Keywords: serum iron